Artificial SEI Film via Synchronous Reaction‐Diffusion‐Assembly on Li Liquid Metal. (18th September 2022) - Wang, Dong; Xie, Tian; Qin, Chichu; Wang, Xianwen; Li, Guanwu; Liu, Yumin; Zou, Haiyan; Huang, Lu; Wu, Yingpeng
Abstract: Solid electrolyte interphase (SEI) is considered as an effective way to suppress Li dendrite. However, most of the constructed SEI films are usually nonuniform and incompact due to the uncertain interface between Li and electrolyte, finally resulting in failure to Li anode protection. To overcome such disadvantage, a stable pristine SEI film is formed successfully by self‐diffusion and assembly when the surface reaction occur between the molten Li and the substrate, benefitting from the ultra‐high chemical activity, atomic level smoothness, and flowability of liquid lithium. It is an inside–outside process via the obtained Li composites migrating from reaction interface to the Li liquid metal surface. Then, the obtained SEI can lead to a stable and long‐lifespan Li integrated electrode, showing the self‐diffusion/assembly strategy upon liquid Li‐metal is a promising way for practical dendrite‐free anode. Abstract : The design conception of artificial solid electrolyte interphase on lithium liquid metal for protection of lithium anodes is proposed, that is, a synchronous reaction‐diffusion‐assembly strategy with the help of the intrinsic characteristics of alkali liquid metal.